"(x-y)p+(y-x-z)q=z\\\\\nz=1, x^2+y^2=1"
Write the system in the symmetric form
"\\frac{dx}{x-y}=\\frac{dy}{y-x-z}=\\frac{dz}{z}\\\\\ni)\\frac{dx}{x-y}=\\frac{dy+dz}{y-x} \\\\\n-dx=dy+dz\\\\\ndx+dy+dz=0\\\\\nd(x+y+z)=0\\\\\nx+y+z=c_1\\\\\nii) x+z=c_1-y\\\\\n\\frac{dz}{z}=\\frac{dy}{y-x-z}\\\\\n\\frac{dz}{z}=\\frac{dy}{y-(x+z)}\\\\\n\\frac{dz}{z}=\\frac{dy}{y-(c_1-y)}\\\\\n\\frac{dz}{z}=\\frac{dy}{2y-c_1}\\\\\n\\int \\frac{dz}{z}=\\int\\frac{dy}{2y-c_1}\\\\\n\\ln|z|+\\frac{1}{2}\\ln|c_2|=\\frac{1}{2}\\ln|2y-c_1|\\\\\nc_2z^2=2y-c_1\\\\\nc_2z^2=2y-x-y-z\\\\\n\\frac{y-x-z}{z^2}=c_2"
General solution is
"F(x+y+z,\\frac{y-x-z}{z^2})=0"
Find particula solution
"\\left\\{\\begin{matrix}\n z=1 \\\\\n x^2+y^2=1\\\\\nx+y+z=c_1\\\\\n\\frac{y-x-z}{z^2}=c_2\n\\end{matrix}\\right.\\\\\n\\left\\{\\begin{matrix}\n x^2+y^2=1\\\\\nx+y+1=c_1\\\\\ny-x-1=c_2\n\\end{matrix}\\right.\\\\\n\\left\\{\\begin{matrix}\n x^2+y^2=1\\\\\nx^2+y^2+2xy=(c_1-1)^2\\\\\nx^2+y^2-2xy=(c_2+1)^2\n\\end{matrix}\\right.\\\\\n\\left\\{\\begin{matrix}\n 1+2xy=(c_1-1)^2\\\\\n1-2xy=(c_2+1)^2\n\\end{matrix}\\right.\\\\\n\\left\\{\\begin{matrix}\n 2xy=(c_1-1)^2-1\\\\\n2xy=1-(c_2+1)^2\n\\end{matrix}\\right.\\\\\n(c_1-1)^2-1=1-(c_2+1)^2\\\\\n(c_1-1)^2+(c_2+1)^2=2"
So particula solution is
"(x+y+z-1)^2+(\\frac{y-x-z}{z^2}+1)^2=2"
Comments
Leave a comment